Hydrogen : a renewable energy perspective (International Renewable Energy Agency, 2019)
Hydrogen has emerged as an important part of the clean energy mix needed to ensure a sustainable future. Falling costs for hydrogen produced with renewable energy, combined with the urgency of cutting greenhouse-gas emissions, has given clean hydrogen unprecedented political and business momentum. This paper from the International Renewable Energy Agency (IRENA) examines the potential of hydrogen fuel for hard-to-decarbonise energy uses, including energy-intensive industries, trucks, aviation, shipping and heating applications. But the decarbonisation impact depends on how hydrogen is produced. Current and future sourcing options can be divided into grey (fossil fuel-based), blue (fossil fuel-based production with carbon capture, utilisation and storage) and green (renewables-based) hydrogen. Green hydrogen produced through renewable-powered electrolysis is projected to grow rapidly in the coming years.
Report prepared for the 2nd Hydrogen Energy Ministerial Meeting in Tokyo, Japan.
"September 2019"
Keywords: Hydrogen as fuel.; Renewable energy sources.; elektronické knihy; electronic books